Bhutan journal of agriculture - Ministry of Agriculture and Forests (Thimphu ; Ministry of Agriculture and Forests, 2019)
The journal provides a platform for researchers to share their findings to wider audience. It is expected to motivate Bhutanese researchers and field colleagues to develop a habit of scientific writing and contribute to knowledge management. It will also serve as a coherent mechanism for sharing appropriate agriculture technologies and knowledge with clients.